Analisis Perbandingan UMKM Pengguna dan Non Pengguna QRIS di Metro Timur - Dwi Gita Cahyani Puja; Isrofia Arbiati; Nia Faradina; Putri Nurvitasari; Zahra Septiani Putri; Esty Apridasari (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the differences in income between Micro, Small, and Medium Enterprises (MSMEs) that use the Quick Response Code Indonesian Standard (QRIS) and those that do not use QRIS in East Metro. The background of this research is based on the rapid development of digital payment systems and the increasing adoption of QRIS as a cashless payment method, which is expected to improve transaction efficiency and business income. The research objects consist of Indra Jaya Store as a QRIS user MSME and Purwanto Store as a non-QRIS user MSME. This study employs a descriptive qualitative approach. Data were collected through observation, interviews, and documentation. Data validity was ensured using source triangulation and technique triangulation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings indicate that there are differences in income between the two MSMEs. Indra Jaya Store, which uses QRIS, earns a monthly gross income of IDR 495,000,000 and a monthly net income of IDR 45,000,000. Meanwhile, Purwanto Store, which does not use QRIS, earns a monthly gross income of IDR 320,000,000 and a monthly net income of IDR 30,000,000. The use of QRIS provides convenience, speed, and flexibility in transactions, thereby increasing customer satisfaction and expanding transaction opportunities. However, the difference in income is not solely influenced by QRIS usage but also by other factors such as business location, number of customers, product variety, and service quality. Based on the findings, it can be concluded that the implementation of QRIS contributes positively to increasing transaction activities and MSME income, while also helping business owners adapt to the growing development of digital payment systems in society.